Adolescencia y psicosis : el empuje a la mujer - León, M. Florencia; Renard, Julieta (2015)
En el marco del proyecto promocional de investigación de la Facultad de Psicología de la Universidad Nacional de La Plata, denominado "Adolescencia: el problema del diagnóstico diferencial en las presentaciones enloquecidas", este trabajo tiene como punto de partida el estudio de la relación entre la adolescencia y la psicosis. En función de tal objetivo, se indagan las formulaciones teóricas de diversos autores que se inscriben en el marco del psicoanálisis, comenzando por Freud, luego por Lacan, hasta llegar a referentes más actuales en la temática como Stoisa, Stevens y Morel entre otros. (Resumen parcial)
Under the promotional research project of the Psychology Department of the UNLP called "Adolescence: the problem of differential diagnosis in presentations of madness", this work has as a starting point the study of the relationship between adolescence and psychosis. In this context there's a study of the revisions of Lacan on Freud's work on this subject, emphasizing what the author calls the second sexual awakening as a discontinuous moment, both at the level of identification, and also at the level of the relations of the subject with sex, and not merely as a reissue of the vicissitudes of child sexuality. We wonder about the relationship between sense and joy in psychotic cases, taking into consideration the works of A. Stevens (1998), who defines adolescence as a symptom of puberty, as a singular episode upon the irruption of that event. For this we focus on the concept of the woman?s lead in psychosis, its scope and relevance in the clinic with psychotic adolescents. (Partial abstract)
Keywords: Adolescencia; Psicosis; Síntoma; Goce